2017
DOI: 10.1186/s13256-017-1366-4
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic colorectal cancer responsive to regorafenib for 2 years: a case report

Abstract: BackgroundRegorafenib is an oral multikinase inhibitor that has been demonstrated as clinically effective in patients with metastatic colorectal cancer in phase III studies. Although disease control was achieved in 40% of the pretreated patients with metastatic colorectal cancer in the pivotal studies, radiological response has rarely been reported. Severe adverse events associated with regorafenib are known to occur during the first and second courses of treatment. We present a case of a 62-year-old Japanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, the CORRECT and CONCUR trials showed that both the PFS and OS of mCRC patients were prolonged following regorafenib treatment, compared with the placebo groups (P<0.0001 and P=0.0016), with a high disease control rate of up to 51% ( 2 , 3 ). Unfortunately, no patients in either study showed a CR, and only a few previously reported cases indicated radiological responses ( 4 , 7 ). More recent studies of regorafenib have reported similar results, with no patients showing a CR and only a few showing a PR (0-3%) ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, the CORRECT and CONCUR trials showed that both the PFS and OS of mCRC patients were prolonged following regorafenib treatment, compared with the placebo groups (P<0.0001 and P=0.0016), with a high disease control rate of up to 51% ( 2 , 3 ). Unfortunately, no patients in either study showed a CR, and only a few previously reported cases indicated radiological responses ( 4 , 7 ). More recent studies of regorafenib have reported similar results, with no patients showing a CR and only a few showing a PR (0-3%) ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 76%
“…As suggested by Yoshino et al ( 4 ), we stopped regorafenib treatment after the 17th cycle due to the lack of remnant tumor evident on both CT and PET-CT. Remarkably, the patient has not experienced recurrence 2 years since treatment cessation; no similar findings have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is advocated that treatment continues until disease progression or unacceptable toxicity levels have been reached, which in some cases, as demonstrated in a recent Japanese case-report, may take several years. 36 Subsequently, approval was granted for management of GIST. Also, approval is almost prohibitively narrow, as it comprises a tumour that is either locally advanced, unresectable or metastatic after treatment with imatinib and sunitinib.…”
Section: Current Approved Uses Of Regorafenibmentioning
confidence: 99%
“…Also, approval is almost prohibitively narrow, as it comprises a tumour that is either locally advanced, unresectable or metastatic after treatment with imatinib and sunitinib. 36,37 Most recently, attention has been drawn to HCC. Similarly, to the two prior approvals, in this case, the scope of the drug is for patients who are candidates for systemic treatment as a second-line treatment after failure or intolerance for sorafenib.…”
Section: Current Approved Uses Of Regorafenibmentioning
confidence: 99%